Investigation and design of an ergonomic wheelchair seat for paraplegic - Muhamad Shukri Tohiran (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The title of this project is investigation and design of an ergonomic wheelchair seat for paraplegic. The project has two main objective, the first is to investigate the condition of the seating to be more ergonomic wheelchairs for paraplegic and the second is to design the seats for wheelchair paraplegic. Based on questionnire and research done, most of paraplegic patients wheelchairs to carry out daily activities.